QUASI-SPONTANEOUS VARIATION OF PHYSICAL PARAMETERS - Rokityansky I.I. (My University, 2001)
Quasi-spontaneous variations are those which appear as though they are spontaneous, but are in fact stimulated by an informational influence, conventionally called 'Z radiation'. An information influence is an influence, the material carrier of which has not been identified, hence its physical natureis not known. The Russian astrophysicist M. O. Kozyrev (1908-1983) showed that when entropy in a system rises and organisation decreases (as it is adopted in thermodynamics, and also leads to the "thermal death" conclusion), then organisation does not vanish, but radiates as a flux of Z radiation. The flux is absorbed by some other system(s) and stimulates processes of self-organisation and evolution in it (them). Sources of Z radiation (i.e. of information influence) are any systems where irreversible processes occur and entropy is rising. These are solar activity (in many instances Z radiation precedes the appearance of corresponding active objects on the Sun's surface), geodynamic and atmospheric processes, technological and biospheric phenomena. A sensor whose emitters (receptors) of Z radiation is any sufficiently self-organised system whose parameters vary noticeably with changes in entropy. Efficient emitters (receptors) are torsion pendulum, quartz, atomic frequency (time) standards, resistors, velocities and some other characteristics of certain quasi-spontaneous processes (radioactive decay, chemical reactions etc.). Geophysical monitoring of quasi-spontaneous variations is regarded as promising for forecasting natural and artificial hazards, periods favorable for human health as well as for biospheric and technological processes.